Five strategies for successful assessment in graduate medical education. Issue 1 (March 2014) - Barlow, Patrick B.; Smith, Tiffany L.; Skolits, Gary
<x xml:space="preserve">Abstract</x> This discussion provides faculty, or anyone conducting their own assessment, with five key strategies for useful assessment in graduate medical education (GME) and the broader higher education environment with or without the benefit of pre‐existing learning objectives. Higher education faculty, including GME, are not trained to develop their own assessment strategies (Hutchings, 2010). Consequently, developing assessment "from the ground up" can be an arduous process, particularly without previous strategies in place. We introduce the strategies using a free‐standing evidence‐based medicine curriculum as a case. The five strategies are: (1) know your situation; (2) clarify your purpose; (3) use what you have; (4) fit the instrument to your purpose, not the other way around; and (5) get consistent and critical feedback. These five strategies should prove beneficial in making sure effective assessment data is gathered efficiently as medical education moves towards a competency‐based model.